Control of radiation-conductive heat exchange at crystal growth from melt - Deshko, V.I.; Karvatskii, A.Ya.; Lenkin, A.V.; Lokhmanets, Yu.V. (Functional Materials, 2008)
The influence of radiation heat exchange in a crystal-melt system for different (from the point of view of optical properties) material classes and crystal growing methods (at constant crystal-melt system thickness and at a constant melt thickness) is considered. The general approach is based on using of modified numerical one-dimensional crystallization model at radiation-conductive heat exchange. The radiation heat transfer in a crystal-melt system provides conditions for faster front movement. In this case, most favorable conditions with large temperature gradients are created in systems with transparent crystal and opaque melt. At simultaneous crystal and melt "transparency" the temperature gradients in melt may decrease and cause stability loss of the directed crystallization.